First Documented Camelus knoblochi Nehring (1901) and Fossil Camelus ferus Przewalski (1878) From Late Pleistocene Archaeological Contexts in Mongolia - Klementiev, Alexey M.; Khatsenovich, Arina M.; Tserendagva, Yadmaa; Rybin, Evgeny P.; Bazargur, Dashzeveg; Marchenko, Daria V.; Gunchinsuren, Byambaa; Derevianko, Anatoly P.; Olsen, John W. (Frontiers in Earth Science, 2022)
Throughout the arid lands of Africa and Eurasia, camelids facilitated the expansion of human populations into areas that would not likely have been habitable without the transportation abilities of this animal along with the organic resources it provides, including dung, meat, milk, leather, wool, and bones. The two-humped, Bactrian, species of Camelus, C. ferus in its wild state and C. bactrianus when domesticated, is much more poorly known in prehistoric archaeological contexts that its single-humped congeneric, C. dromedarius. Our research uses a convergence of evidence approach to analyze reports and remains of Plio-Pleistocene camelids in Central and Northern Asia and trace the latest-known fossil Bactrian relative, Camelus knoblochi, that seems to have survived in the Gobi Desert until the Last Glacial Maximum (ca. 26.5-19 ka). We also consider the validity of a reported fossil of C. sivalensis from Mongolia. Rock art depictions, some of which may be of Pleistocene age, record the complexity of nascent human-camel interactions and provide the impetus for further archaeological studies of both the origins of C. bactrianus and its increasingly complex relationships with the highly mobile prehistoric peoples of Central and Northern Asia.